2017
DOI: 10.3390/su9071251
|View full text |Cite
|
Sign up to set email alerts
|

Waste Management in Industrial Construction: Investigating Contributions from Industrial Ecology

Abstract: The need for effective construction waste management is growing in importance, due to the increasing generation of construction waste and to its adverse impacts on the environment. However, despite the numerous studies on construction waste management, recovery of construction waste through Industrial Symbiosis and the adoption of other inter-firm practices, comprised within Industrial Ecology field of study, have not been fully explored. The present research aims to investigate Industrial Ecology contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Core practices cover the major stages of the construction supply chain, including design, purchasing, transportation, construction and end-of-life management. These practices involve considerations such as the development of green building materials [101], prudent use of natural resources [16], the adoption of offsiteprefabrication [4], waste management planning [102,103] and reverse logistics [104,105], among many others. On the other hand, facilitating practices, which support core practices, consist of environmental management systems and certifications (e.g., policies, assessments, etc.…”
Section: Best Practicesmentioning
confidence: 99%
“…Core practices cover the major stages of the construction supply chain, including design, purchasing, transportation, construction and end-of-life management. These practices involve considerations such as the development of green building materials [101], prudent use of natural resources [16], the adoption of offsiteprefabrication [4], waste management planning [102,103] and reverse logistics [104,105], among many others. On the other hand, facilitating practices, which support core practices, consist of environmental management systems and certifications (e.g., policies, assessments, etc.…”
Section: Best Practicesmentioning
confidence: 99%
“…Bagheri, et al (2015) also noted that analysis of previously recorded data could be used to determine the issues in the previous process and help forecast the future challenges that might arise and strategies towards mitigating these issues. Freitas and Magrini (2017) observed that business activities could be analysed with BDA in the construction industry to determine the optimal phasing of construction activities. Furthermore, data generated from the thousands of sensors installed in buildings and/or moving drones, bridges and any other construction project makes it possible to monitor each one at any level of performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…By 2010, 26 countries had become the focus of attention in articles, and by 2017, specific by-product exchanges had been reported for 89 industrial clusters in 20 countries in these articles (Figure 4). South America, Africa, and the Middle East, including Brazil (Ceglia, de Abreu, & Da Silva Filho, 2017;de Oliveira, França, & Rangel, 2018;Elabras Veiga & Magrini, 2009;Freitas & Magrini, 2017;Ometto, Ramos, & Lombardi, 2007;Santos & Magrini, 2018), Colombia (J. Park et al, 2018), Egypt (ElMassah, 2018Sakr, Baas, El-Haggar, & Huisingh, 2011), Ghana (Medina-GonzĂĄlez, Graells, GuillĂ©n-GosĂĄlbez, Espuña, & Puigjaner, 2017), Liberia (Alfaro & Miller, 2014), Mauritius (Mauthoor, 2017;Mutanga, de Vries, Mbohwa, Das, & Rogner, 2016), South Africa (Greenberg & Rogerson, 2014),…”
Section: Geographical Distributionmentioning
confidence: 99%